Metal cutting theory and practice - Stephenson, David A. (Manufacturing engineering and materials processing, 1997)
Provides insight into advanced tool materials, physical theory and research understanding of metal cutting processes. The text highlights technology developed internationally, and reviews available technology of metal cutting processes, such as turning, boring, milling and drilling. It also elucidates optimum choices for tool material and cutting conditions, and more.